2021
DOI: 10.1080/00220671.2021.1929052
|View full text |Cite
|
Sign up to set email alerts
|

Student evaluations of the credibility and argumentation of online sources

Abstract: This study investigated upper secondary school students' skills in evaluating the credibility and argumentative content of a blog text and a YouTube video. Both sources concerned child vaccination, the blog text opposing and the YouTube video supporting it. Students rated each source as credible, fairly credible or non-credible, justified their ratings, and analyzed the argumentation of both sources. Their justifications were analyzed for trustworthiness and expertise and their argument analyses for identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
2
6
0
1
Order By: Relevance
“…An exception is the work by Wittenberg et al (2021), who found, across two studies, that the presented information was perceived as more believable for learners confronted with a video than for learners confronted with a text in the context of political and healthrelated topics. One other study by Marttunen et al (2021) showed that secondary school students performed poorly in justifying their evaluation of credibility and argumentative content of both video and text-based online sources. However, participants showed even poorer performance in justifying why a source was less credible for a video resource than for a text resource.…”
Section: Source Reputationmentioning
confidence: 99%
“…An exception is the work by Wittenberg et al (2021), who found, across two studies, that the presented information was perceived as more believable for learners confronted with a video than for learners confronted with a text in the context of political and healthrelated topics. One other study by Marttunen et al (2021) showed that secondary school students performed poorly in justifying their evaluation of credibility and argumentative content of both video and text-based online sources. However, participants showed even poorer performance in justifying why a source was less credible for a video resource than for a text resource.…”
Section: Source Reputationmentioning
confidence: 99%
“…Therefore, facilitating teachers' learning needs is needed as scaffolding (Vogel et al, 2022) for students through the learning process (Lase, 2019) Scaffolding through the learning process is important because using digital devices for learning tools in accessing, evaluating, and using information validity of online learning resources is still a challenge for students (Barrot et al, 2021). In particular, the skills to analyze and evaluate information sources are proven inadequate (Marttunen et al, 2021). In addition, students also experience difficulties in understanding argumentation, especially the role of warrants in scientific argumentation (Martín-Gámez & Erduran, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Students must be able to compile strong evidence warrants to make claims about a problem or issue they face, so facilitating the practice of argumentation in learning is needed to improve it (Yilmaz et al, 2017). Improving students' ability to assess the credibility of sources and recognizing arguments from reference sources that involve interpretation and analysis of online information is crucial because it is an information processing stage (Marttunen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents search less systematically ( Bilal and Kirby, 2002 : 661–663; Hansen et al, 2003 : 7), their search is superficial, and they seldom consider the source of the information ( Hansen et al, 2003 : 7; Wallace et al, 2000 : 93–94). It seems that adolescents’ skills are rather inadequate and insufficient ( Marttunen et al, 2021 : 300–301). When evaluating sources, their assessments are focused more on relevance or accessibility (non-epistemic justification) than reliability or credibility (epistemic justification) ( Coiro et al, 2015 : 294; List et al, 2016 : 47).…”
Section: Introductionmentioning
confidence: 99%